Uniaxial Fatigue of HDPE-100 Pipe. Experimental Analysis - Djebli, A.; Aid, A.; Bendouba, M.; Talha, A.; Benseddiq, N.; Benguediab, M.; Zengah, S. (Engineering, Technology & Applied Science Research, 2014)
In this paper, an experimental analysis for determining the fatigue strength of PE-100, one of the most used High Density Polyethylene (HDPE) materials for pipes, under cyclic axial loadings is presented. HDPE is a thermoplastic material used for piping systems, such as natural gas distribution systems, sewer systems and cold water systems, which provides a good alternative to metals such as cast iron or carbon steel. One of the causes for failures of HDPE pipes is fatigue which is the result of pipes being subjected to cyclic loading, such as internal pressure, weight loads or external loadings on buried pipes, which generate stress in different directions: circumferential, longitudinal and radial. HDPE pipes are fabricated using an extrusion process, which generates anisotropic properties. By testing in the Laboratory a series of identical specimens obtained directly from PE-100 HDPE pipes in longitudinal directions, the relationships between amplitude stress and number of cycles (S-N curve) test frequency 2 Hz and stress ratio R = 0.0 are established.